Prentice Hall literature : timeless voices, timeless themes silver level, 8 - Don Graham, et. al.; Linda Ellis;Jacqueline Gerla;Joyce Caroll;Edward Wilson;Richard Lederer;Angelia Guadarrama (Unites States of America : Prentice Hall Inc., 2001)
Throughout their state's rich history, Texas writers have recorded their hopes and dreams, struggles and triumphs. The stories, essays, poems and plays in this unit range from classic to contemporary, and reflect a diversity of cultures and experiences. Despite their variety, however, in each of this selections, you will hear the voices of Texas.
Unit1. Coming of Age -- Unit2. Meeting Challenges -- Unit3. Quest for Justice -- Unit4. From Sea to Shinning Sea -- Unit5. Extraordinary Occurrences -- Unit6. Short Stories -- Unit7. Nonfiction -- Unit 8. Drama -- Unit9. Poetry -- Unit10. The American folk Tradition.
Includes index.
Keywords: LITERATURE